Separation of enantiomers of Baclofen - Wildervanck, Alexander Franciscus (Department of Chemistry, 2016)
(3-(Aminomethyl)-4-chlorobenzenepropanoic acid (Baclofen), 3-(p-chlorophenyl)pyrrolidone (Baclofen lactam) and 3-(p-Chlorophenyl)glutaramide (baclofen's synthetic precursor) were individually used as substrates in co-crystallisation experiments with several resolving agents. Experiments were conducted in the solid state and in solution. The (-) enantiomer of the lactam and the ( +) enantiomer of the glutaramide were found to cocrystallise selectively with (2R,3R)-( +)-tartaric acid and (S)-(-)-a.-Methylbenzylamine respectively. Both these dissociable diastereomers Vere analysed by X-ray crystallography. HPLC analysis of the lactam retrieved from the former co-crystals indicated only partial separation of its (+) and (-) enantiomers. X-ray crystallographic, thermal, and polarimetric analyses were perfom1ed on the ( + )- and (-)-salts of the latter co-crystals. The solubilities of these salts in methanol were found to differ by a factor of 4. A solubility diagram was established showing the phase equilibria of various ratios of these two salts in methanol. The(+) enantiomer of the glutaramide was separated from the methylbenzylamine in the (+) salt by treatment with HCI. This enantiomer was converted to (R)-(-)-Baclofen by means of a Hofinann Rearrangement with an overall yield of 40%. The enantiomeric excess of (R)-(".")-Baclofen was 99.7%.